Diagnostic value of multi-tumor-associated autoantibody expression in esophageal squamous cell carcinoma and correlation of clinical features - Zhou, Sihao; Liu, Kejun; Yang, Yuyu; Yuan, Chuan; Liu, Yi; Liang, Yi; Li, Wenhao; Zhang, Jingjing; Ye, Hongyu; Gong, Sheng; Wu, Yingmeng; Huang, Weizhao (Frontiers in Immunology, 2024)
ObjectiveThis study aimed to investigate the diagnostic value of 7-tumor associated autoantibodies (7-TAAB) and to evaluate the relationship between 7-TAAB and clinical features in esophageal squamous cell carcinoma (ESCC), which can be used to guide clinical diagnosis and treatment and achieve its clinical value.Methods(1) Blood specimens were collected from patients with ESCC who had not previously received antitumor therapy (ESCC group) and those who had normal medical check-ups in the hospital during the same period (control group). The concentrations of 7-TAAB (P53, PGP9.5, SOX2, GAGE7, GBU4-5, MAGE A1, and CAGE) in serum were determined by enzyme-linked immunosorbent assay. The concentrations of 7-TAAB were compared between the ESCC and control groups, and the positive rate of 7-TAAB was calculated to determine the sensitivity, specificity, and accuracy of 7-TAAB. The diagnostic value of 7-TAAB was analyzed using the receiver operating characteristic (ROC) curve. (2) The clinical data of patients with ESCC were collected and the correlation between the rate of 7-TAAB and clinical features was analyzed.Results(1) The serum levels and positivity rates of five antibodies (PGP9.5, SOX2, GBU4-5, MAGE-A1, and CAGE) were higher in the ESCC group than in the control group (P < 0.05) and the positive expression rate of the combined serum 7-TAAB in the ESCC group was significantly higher than that in the control group (P < 0.05). (2) The sensitivity of single antibody detection was 4.20%–17.65%, with a specificity of 96.49%–100%, and accuracy of 51.07%–57.94%. The sensitivity of 7-TAAB combined detection was 49.58%, the specificity was 92.98%, and the accuracy was 70.81%. (3) The ROC curve showed that the 7-TAAB combined test had a certain diagnostic value for ESCC and that its diagnostic efficacy was significantly higher than that of the single autoantibody tests. The diagnostic efficacy of the combined test with the remaining five antibodies (PGP9.5, SOX2, GBU4-5, MAGE-A1, and CAGE) was similar to that of the 7-TAAB combined test after eliminating the two antibodies with low expression rates. (4) Univariate analysis revealed significant differences in the positive expression rates of the 7-TAAB combination test in terms of age, hemoglobin level, albumin level, tumor location, tumor length, lymph node stage, and tumor clinical stage (P < 0.05), and multivariate analysis revealed that age and lymph node stage were independent factors affecting antibody expression.ConclusionThe multi-tumor-associated autoantibody combination test not only has a good auxiliary diagnostic value but also closely correlates with the clinical features of ESCC.